Child rights in India : law, policy, and practice - Bajpai, Asha. (New Delhi ; Oxford : Oxford University Press, 2006)
This comprehensive volume serves as a basic resource book, which examines both the existing legislation and recommends future reforms for the protection of child rights.
Previous ed.: 2003.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Children -- Legal status, laws, etc. -- India